The gains from trade and the gains from aid : essays in international trade theory - Kemp, Murray C. (London ; New York : Routledge, 1995)
Comprises previously published essays written over a period of 35 years.
1. The Gain from International Trade -- 2. The Gains from Free Trade / Murray C. Kemp and Henry Y. Wan, Jr. -- 3. An Elementary Proposition Concerning the Formation of Customs Unions / Murray C. Kemp and Henry Y. Wan, Jr. -- 4. The Comparison of Second-Best Equilibria: The Case of Customs Unions / Murray C. Kemp and Henry Y. Wan, Jr. -- 5. The Gains from Trade When Markets are Possibly Incomplete / Murray C. Kemp and Kar-yiu Wong -- 6. The Gains from Free Trade for a Monetary Economy -- 7. The Gains from Trade for a Monetary Economy When Markets are Possibly Incomplete / Murray C. Kemp and Kar-yiu Wong -- 8. Trade Gains in a Pure Consumption-Loan Model -- 9. Gains from Trade with Overlapping Generations / Murray C. Kemp and Kar-yiu Wong -- 10. The Gains from International Trade in a Context of Overlapping Generations / Murray C. Kemp and Nikolaus Wolik -- 11. The Welfare Gains from International Migration.
Includes bibliographical references and indexes.
Keywords: International trade; International economic relations; Equilibrium (Economics); Commerce international; Equilibrium (Economics); International economic relations; International trade; 2; Wohlfahrt; Aufsatzsammlung; Internationale handel; Marktvormen; Ontwikkelingssamenwerking; trade; economic theory; economic model; free trade; trade barrier; comparative advantage; competition; economic equilibrium; development aid; statistical table; 2; Commerce international; 2; commerce international; 2; 2; 2; 2; 2; concurrence; 2; 2; tableau statistique; comercio internacional; 2; 2; libre comercio; barrera comercial; ventaja comparativa; competencia; 2; ayuda al desarrollo; 2; Foreign trade; Aufsatzsammlung; bibliography; graph; illustration; illustration; bibliographie; graphique; 2; 2; 2